Upper Canada’s Union Debates (1822-23, 1839-40): Facing the ‘French Fact’ - Russell, Peter (Ontario History)

(untitled) (The Ontario Historical Society, 2023)
The Upper Canadian Assembly’s two debates on union with Lower Canada, especially the first, show a much greater range of views towards it than contemporaries expected. Leading members upheld the unique national character of French Canada, denouncing Britain’s attempt to use their colony to suppress another. The first debate grew out of attempts originating in a Whig member of the opposition to solve the division of customs revenue between the two, breaking the deadlock that already characterized the lower province. The second, much more strained came in the wake of the 1837 Rebellions with union as a government project to ‘put down the French’. While the second bill passed, its implementation failed as, once again, Upper Canadian members of the assembly refused the play the role in which the British government had cast them.